2016
DOI: 10.5897/jmpr2015.5993
|View full text |Cite
|
Sign up to set email alerts
|

Schistosomicidal and molluscicidal activities of two Junipers species cultivated in Egypt and the chemical composition of their essential oils

Abstract: In the present study, in vitro bioassay screening of total methanolic extracts of two Juniperus species (Juniperus horizontalis Moench. and Juniperus communis L.) cultivated in Egypt for schistosomicidal and molluscicidal activities was carried out. Schistosoma mansoni Sambon worms and Biomphalaria alexandrina (Ehrenberg) snails were used. The screening results showed that both tested extracts had almost similar schistosomicidal activity (LC50 ≈ 91 µg/ml, in 3 days) while J. communis extract possess more poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…(2016)Ethyl acetate fraction of J. communis leavesCell viability assay on HepG2 cellsFraction in WST-1 proliferation assay didn't affect HepG2 cell viability after treatment for 24 h at a concentration between 0-10 μg/mlVed et al. (2017)Extract of areal part of J. communis In-vitro assay on Human prostate cancer cells (PC-3), Human colon cancer cells (HCT-116) and mammary cancer cells (MCF-7) using MTTHighest activity with the safest margin observed for the total methanolic extract against human breast cancer cell line (MCF-7)Ghaly et al. (2016)Diterpenes isocupressic and aryltetralin lignan deoxypodophyllotoxin from J. communis Malignant – MB231 breast cancer cellsInduced caspase dependent programmed cell death (apoptosis); aryltetralin lignan deoxypodophyllotoxin inhibited cell survival pathways mediated by the MAPK/ERK and NK-kß signaling pathways within hours of treatmentBenzina et al.…”
Section: Discussionmentioning
confidence: 99%
“…(2016)Ethyl acetate fraction of J. communis leavesCell viability assay on HepG2 cellsFraction in WST-1 proliferation assay didn't affect HepG2 cell viability after treatment for 24 h at a concentration between 0-10 μg/mlVed et al. (2017)Extract of areal part of J. communis In-vitro assay on Human prostate cancer cells (PC-3), Human colon cancer cells (HCT-116) and mammary cancer cells (MCF-7) using MTTHighest activity with the safest margin observed for the total methanolic extract against human breast cancer cell line (MCF-7)Ghaly et al. (2016)Diterpenes isocupressic and aryltetralin lignan deoxypodophyllotoxin from J. communis Malignant – MB231 breast cancer cellsInduced caspase dependent programmed cell death (apoptosis); aryltetralin lignan deoxypodophyllotoxin inhibited cell survival pathways mediated by the MAPK/ERK and NK-kß signaling pathways within hours of treatmentBenzina et al.…”
Section: Discussionmentioning
confidence: 99%
“…Synthetic pesticides lead to environmental pollution and pest resistance with their effects on the beneficial living organisms and phytotoxicity. The toxic effect of plant extracts against the land snail Monacha obstructa was reported by other researchers (Speiser et al 1992;Ghamry 1997;Dodds and Hendrson 2002;Ebenso 2004;Shabad 2010;Anjali et al 2014;Ghaly 2016 andDing et al 2018). The objective of the present investigation is to study the molluscicidal effect of three weed extracts namely primpernel , nightshade and nutsedge against the adult stage of land snail M. obstructa as well as identification of chemical components of the more active extract using GC/MS analysis.…”
Section: Introductionmentioning
confidence: 68%
“…Moreover, Dodds and Hendrson (2002) whom indentified eleven antifeedant chemicals from plants including phenols, alcohols, ketones, aldhydes and steroids, suggesting that slug or snail feeding may be controlled by these chemicals. In this respect, Ghaly et al (2016) who identified sixty seven components by GC/MS in Juniperus communis oil with homogeraniol (36.9%) as the major constituent while sixty components were identified in J. horizontalis oil with the main component, bronylacetate representing 41.2%. Two Juniperus species appeared molluscicidal activities.…”
Section:  Identification Of Chemical Components In the Chloroform Extract Of Primpernel By Gc/ms Analysismentioning
confidence: 99%
“…The oil content obtained by hydro-distillation of the aerial parts of J. horizontalis representing 0.75% v/w was analyzed using GC/MS showing a total of 60 compounds (Ghaly et al, 2016). Bornyl acetate was seen as a major component representing 41.17% followed by 10-epielemol representing 8.44% and β-myrcene 5.94%, sabenine 5.51% and thujone 4.8%.…”
Section: Introductionmentioning
confidence: 99%